In silico molecular docking of luteolin as a potential antihyperpigmentation agent - Putri, Lucienne Agatha Larasati Nugraha; Anjani, Ni Luh Ari Krisma; Laksmiani, Ni Putu Linda; Susanti, Ni Made Pitri (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Excessive melanin synthesis, often triggered by overexposure to UV rays, is catalyzed by melanogenesis enzymes such as tyrosinase, tyrosinase-related protein 1, and D-dopachrome tautomerase. Derived from natural sources, the flavonoid compound luteolin is explored for its antihyperpigmentation potential. This study assesses luteolin’s efficacy as an antihyperpigmentation agent by analyzing its affinity and bond interactions with melanogenesis enzymes through an in silico approach. Molecular docking, facilitated by HyperChem 8 for test compound optimization and Chimera 1.11.1 for protein preparation, alongside method validation and docking with AutoDockTools 1.5.6, established the protocol’s validity with an RMSD value of ≤3 Å. Docking results reveal luteolin's higher affinity for the target proteins compared to native ligands, with binding energies of -5.63 kcal/mol for tyrosinase, -6.18 kcal/mol for tyrosinase-related protein 1, and -6.54 kcal/mol for D-dopachrome tautomerase. The interaction between luteolin and these proteins involves hydrogen, hydrophobic, electrostatic, and Van der Waals bonds, with amino acid residues His61, Lys129, Arg132 (tyrosinase); His192, His224, Val89 (tyrosinase-related protein 1); and Ile64, Asn73 (D-dopachrome tautomerase) participating in hydrogen bond formation. These findings suggest luteolin’s significant potential as an antihyperpigmentation agent by inhibiting melanogenesis enzymes.